The Future of VGI - Antoniou, Vyron (2017)
In this final chapter, we speculate on future developments in the field of Volunteered Geographic Information (VGI); we focus on how VGI will be a affected by future technological developments, but we also consider issues such as VGI quality, the relationship of VGI with science and citizens, and the impact of VGI in future cities and societies.